Transient CNS responses to repeated binge ethanol treatment. (18th August 2015) - Zahr, Natalie M.; Rohlfing, Torsten; Mayer, Dirk; Luong, Richard; Sullivan, Edith V.; Pfefferbaum, Adolf
Abstract: The effects of ethanol (EtOH) on in vivo magnetic resonance (MR)‐detectable brain measures across repeated exposures have not previously been reported. Of 28 rats weighing 340.66 ± 21.93 g at baseline, 15 were assigned to an EtOH group and 13 to a control group. Animals were exposed to five cycles of 4 days of intragastric (EtOH or dextrose) treatment and 10 days of recovery. Rats in both groups had structural MR imaging and whole‐brain MR spectroscopy (MRS) scans at baseline, immediately following each binge period and after each recovery period (total = 11 scans per rat). Blood alcohol level at each of the five binge periods was 300 mg/dl. Blood drawn at the end of the experiment did not show group differences for thiamine or its phosphate derivatives. Postmortem liver histopathology provided no evidence for hepatic steatosis, alcoholic hepatitis or alcoholic cirrhosis. Cerebrospinal fluid volumes of the lateral ventricles and cisterns showed enlargement with each binge EtOH exposure but recovery with each abstinence period. Similarly, changes in MRS metabolite levels were transient: levels of N ‐acetylaspartate and total creatine decreased, while those of choline‐containing compounds and the combined resonance from glutamate and glutamine increased with each binge EtOH exposure cycle and then recovered during each abstinence period. Changes in response to EtOH were in expected directions based on previous single‐binge EtOH exposure experiments, but the current MR findings do not provide support for accruing changes with repeated binge EtOH exposure. Abstract :